GROUNDWATER POLLUTION SOURCE USING PRINCIPAL COMPONENT ANALYSIS IN GUELMA PLAIN, NORTHEAST ALGERIA - Baazi Houria; Nemili Zohra; Necer AbdeLdjabar; Saoudi Messaoud (International Journal of Innovative Technologies in Social Science, 2024)
This study was conducted in the agricultural region of Guelma, located in northeastern Algeria, where groundwater is the main source of water for human consumption, agriculture, and industry. The objective was to characterize groundwater quality and identify potential pollution sources using multivariate statistical methods, including Principal Component Analysis (PCA), correlation matrix, and the Piper diagram. The analyses revealed strong correlations between certain ions, such as sodium and chloride, suggesting carbonate dissolution processes, such as calcite and dolomite, leading to increased water hardness. The Piper diagram allowed for the classification of water types based on the relative concentrations of major cations (Ca²⁺, Mg²⁺, Na⁺+K⁺) and anions (Cl⁻, SO₄²⁻, CO₃²⁻+HCO₃⁻), showing a predominance of mixed hydrochemical types influenced by both natural and anthropogenic processes.PCA then simplified the interpretation by identifying the most influential variables that could serve as key indicators for the continuous monitoring of water quality. Overall, the results indicate that groundwater chemistry in this region is strongly influenced by human activities and local geological conditions, highlighting the need for sustainable management and continuous monitoring to protect this vital resource.